Longitudinal Follow-Up of Children Born Preterm: Neurodevelopment From 2 to 10 Years of Age - Jansen, Lisette; Peeters-Scholte, Cacha M. P. C. D.; Berg-Huysmans, Annette A. van den; Klink, Jeanine M. M. van; Rijken, Monique; Egmond-van Dam, Janneke C. van; Vermeiren, Robert R. J. M.; Steggerda, Sylke J. (Frontiers in Pediatrics, 2021)
Objective To investigate the rate and stability of impairments in children born preterm by assessing 1) early and school-age outcome in four developmental domains, 2) individual changes in outcome at both timepoints, and 3) who is at risk of moderate-severe impairment. Design Prospective, longitudinal cohort study in children born <32 weeks’ gestation. Follow-up at two and ten years of age included standardized neurological, motor, cognitive and behavioral assessments. Children were categorized as having no, mild or moderate-severe impairment in these four domains. A composite impairment score was composed and the number of domains with impairments counted. For each child, individual outcomes at both timepoints were compared. Results Follow-up at both time-points was available in 71/113(63%) children. At group level, there were no significant changes in the severity of impairments per domain. However, at individual level , there were less children with a mild abnormal composite score at ten years of age (44% vs 20%; p =.006), and more with a moderate-severe abnormal composite score (12% vs 35%; p =.001). Especially children with normal/mild outcome at two years were likely to shift to other outcome categories over time. Risk-factors for moderate-severe impairment at age ten included low birthweight, bronchopulmonary dysplasia and/or white matter injury. Conclusions Children with early severe impairment are likely experiencing impairments later on, but early normal/mild abnormal outcomes should be interpreted with care, considering the large individual shifts over time. Long-term follow-up in all children born very preterm should therefore be continued to at least school-age.